La prosa dell'ermetismo: caratteri e esemplari - Nencioni, Francesca (Premio Ricerca «Città di Firenze», 2016)
In this book, Francesca Nencioni uses semantics to reconstruct, with skill and intelligence, the 'characters' and 'specimens' of the Hermetic prose (Parronchi, I giorni sensibili; Luzi, Biografia e Ebe; Bigongiari, La donna miriade; Gatto, La sposa bambina), proposing a new way of reading the works which marked the early Hermetic period in Florence. Using stylistic tools, analysis of language, rhythm and melody, and a comparative perspective shifting continuously among the genres, the author gives new semantics to the category of absence (through female metamorphosis, transience and death), and explores the coordinates of time (the hours of day, the movements of stars and planets, the alternation of seasons) and space (the four elements, the beloved places and the real landscapes), then combines synchronic investigation with an excursus on the study of semantic variables in the two editions of Biografia e Ebe and La sposa bambina.